2020
DOI: 10.1002/aoc.5701
|View full text |Cite
|
Sign up to set email alerts
|

Two new micro‐isostructural metal–organic polymers based on mixed‐ligand copper(I): Structures and selective sensing of nitro explosives in water

Abstract: Two new one-dimensional metal-organic polymers (MOPs) {[Cu(L) (PPh 2 Py)•I 2 ]•CH 3 Cl} n (I) and {[Cu(L)(PPh 2 Py)•Br 2 ]•CH 3 Cl} n (II) (L = (1E,2E)-1,2-bis(pyridine-4-ylmethylene)hydrazine) (4-bpmh)) have been synthesized and elucidated by single crystal X-ray diffraction. The results of X-ray diffraction analysis unambiguously revealed that the two polymers are isostructural with the major intermolecular CHÁ Á Áπ and πÁ Á Áπ interactions. Microstructures of these polymers were also synthesized using a son… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 56 publications
1
1
1
Order By: Relevance
“…Recognition of various nitrophenols is also an important part of recovery and reuse, so it is necessary to carry out sensitive fluorescence sensing and recognition of nitrophenols. Gholivand et al synthesized two metal–organic polymers (MOPs), {[Cu­(L)­(PPh 2 Py)·I 2 ]·CH 3 Cl} n ( I ) and {[Cu­(L)­(PPh 2 Py)·Br 2 ]·CH 3 Cl} n ( II ) (L = (1 E ,2 E )-1,2-bis­(pyridine-4-ylmethylene)­hydrazine), and the two MOPs were used as luminescent sensors for 4-nitrophenol sensitivity and selectivity . However, integrated multifunctional fluorescent materials for sensing and recognition of nitrophenols and white light emission are resource saving.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Recognition of various nitrophenols is also an important part of recovery and reuse, so it is necessary to carry out sensitive fluorescence sensing and recognition of nitrophenols. Gholivand et al synthesized two metal–organic polymers (MOPs), {[Cu­(L)­(PPh 2 Py)·I 2 ]·CH 3 Cl} n ( I ) and {[Cu­(L)­(PPh 2 Py)·Br 2 ]·CH 3 Cl} n ( II ) (L = (1 E ,2 E )-1,2-bis­(pyridine-4-ylmethylene)­hydrazine), and the two MOPs were used as luminescent sensors for 4-nitrophenol sensitivity and selectivity . However, integrated multifunctional fluorescent materials for sensing and recognition of nitrophenols and white light emission are resource saving.…”
Section: Introductionsupporting
confidence: 86%
“…44 Recognition of various nitrophenols is also an important part of recovery and reuse, so it is necessary to carry out sensitive fluorescence sensing and recognition of nitrophenols. Gholivand 45 However, integrated multifunctional fluorescent materials for sensing and recognition of nitrophenols and white light emission are resource saving.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thus, we explored the detection effect of Cd-MOF on some NACs, and the results showed that 2,4,6-trinitrophenol (TNP), 2,4-dinitrophenol (DNP), p -dinitrobenzene ( p -DNB), o -dinitrobenzene ( o -DNB), p -nitrophenol phenol (PNP), and o -nitrophenol (ONP) could significantly quench the fluorescence of Cd-MOF. Among them, the detection limits of Cd-MOF for TNP, DNP, and PNP were 0.089, 0.092, and 0.016 μM, respectively, which were lower than the detection limits of similar materials reported in literature. In addition, we also found that Cd-MOF has the ability to distinguish OPD, MPD, and PPD through fluorescence property experiments and could be used as a selective fluorescence sensor to detect OPD and MPD.…”
Section: Introductioncontrasting
confidence: 52%